2022
DOI: 10.3390/cancers14061574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osimertinib on CTCs and ctDNA in EGFR Mutant Non-Small Cell Lung Cancer Patients: The Prognostic Relevance of Liquid Biopsy

Abstract: Introduction: Liquid biopsy is a useful tool for monitoring treatment outcome in solid tumors, including lung cancer. The relevance of monitoring CTCs and plasma ctDNA as predictors of clinical outcome was assessed in EGFR-mutant NSCLC patients treated with osimertinib. Methods: Forty-seven EGFR-mutant NSCLC patients who had progressed on prior first- or second-generation EGFR inhibitors were enrolled in the study and treated with osimertinib, irrespective of the presence of the T790M mutation in the primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In a previous study of our group, CK + CTCs were identified by IF on ISET filters from 30 chemo-naïve stage IV NSCLC patients at baseline, before front-line chemotherapy (57% of patients), and after the third cycle of treatment (73%) [ 18 ]. In addition, in another of our studies, 69% of NSCLC patients treated with Osimertinib had CTCs isolated by ISET [ 5 ]. In the current study, 62% (26 out of 42) of patients had at least one CTC at some point in the evaluation, which is comparable to Kallergi et al (2022).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a previous study of our group, CK + CTCs were identified by IF on ISET filters from 30 chemo-naïve stage IV NSCLC patients at baseline, before front-line chemotherapy (57% of patients), and after the third cycle of treatment (73%) [ 18 ]. In addition, in another of our studies, 69% of NSCLC patients treated with Osimertinib had CTCs isolated by ISET [ 5 ]. In the current study, 62% (26 out of 42) of patients had at least one CTC at some point in the evaluation, which is comparable to Kallergi et al (2022).…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, CTCs’ detection and enumeration have been proven to be a useful prognostic tool for both early and advanced NSCLC, with even one CTC being an independent risk factor for recurrence and death [ 4 ]. We have recently showcased the complementarity of CTC and ctDNA analysis in NSCLC patients treated with Osimertinib, whereby both are decreased after one cycle of treatment and increased at the end of treatment (EOT), which coincided with the progression of the disease [ 5 ]. Osimertinib is a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Tumor cells that are malignant, shed by solid tumors into the bloodstream, are commonly referred to as circulating tumor cells (CTCs), which are valuable in providing indicative evaluation information for therapeutic efficacy, cancer prognosis or metastases and therefore considered a prognostic biomarker for diagnosis. 3–6…”
Section: Introductionmentioning
confidence: 99%
“…2 Tumor cells that are malignant, shed by solid tumors into the bloodstream, are commonly referred to as circulating tumor cells (CTCs), which are valuable in providing indicative evaluation information for therapeutic efficacy, cancer prognosis or metastases and therefore considered a prognostic biomarker for diagnosis. [3][4][5][6] However, since the number of CTCs in blood is extremely small, how to successfully and reliably capture them from the complex blood media is a critical step for downstream analysis. [7][8][9][10][11][12] Compared with the common capture methods established according to some physical properties, such as cell size, 13 density, 14 and permittivity, 15 an affinity-based strategy is more popularly employed in CTC isolation, taking advantage of the specific interactions between the recognition ligands (antibody, 16 aptamer, 17 peptide, 18 etc.)…”
Section: Introductionmentioning
confidence: 99%